2021
DOI: 10.22438/jeb/42/3/mrn-1498
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration potential under tea based cropping system

Abstract: Aim: To study the carbon sequestration process in tea based plantation system and to identify more potential carbon sequestration system amongst the tea based cropping system by studying carbon storage in different components of the plantation system. Methodology: The experiment was carried out in the Experimental Garden for Plantation Crops of Assam Agricultural University, Jorhat, Assam. Treatments were made in an on going, long term shade experiment on mature tea bushes, adapted to three levels of shades v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It was found that, tea bushes sequestrated 5134.4 ± 831.6 kg CO 2 ha −1 year −1 in their biomass and had global warming mitigation potential (GWMP) of 3.47 ± 0.64 kg CO 2 KMTH −1 year −1 . Alom et al (2021) showed that, among various cropping systems, tea-albizzia cropping system had superior performance in carbon sequestration followed by tea-areca palm cropping system with respect to monoculture in the north eastern states of India. While several works were going on regarding the carbon sequestration potential of tea plantations in the north eastern states of India, Kumari et al (2021) showed the potential of renewable energy technologies to mitigate the problem of global warming in the tea plantations of north eastern India using some basic descriptive statistics on a pilot survey data.…”
mentioning
confidence: 99%
“…It was found that, tea bushes sequestrated 5134.4 ± 831.6 kg CO 2 ha −1 year −1 in their biomass and had global warming mitigation potential (GWMP) of 3.47 ± 0.64 kg CO 2 KMTH −1 year −1 . Alom et al (2021) showed that, among various cropping systems, tea-albizzia cropping system had superior performance in carbon sequestration followed by tea-areca palm cropping system with respect to monoculture in the north eastern states of India. While several works were going on regarding the carbon sequestration potential of tea plantations in the north eastern states of India, Kumari et al (2021) showed the potential of renewable energy technologies to mitigate the problem of global warming in the tea plantations of north eastern India using some basic descriptive statistics on a pilot survey data.…”
mentioning
confidence: 99%